Structural and electrical-physical properties of the ohmic contacts based on palladium to n⁺ -n-n⁺⁺ -n⁺⁺⁺ -InP - Belyaev, A.E.; Boltovets, N.A.; Bobyl, A.B.; Kladko, V.P.; Konakova, R.V.; Kudryk, Ya.Ya.; Nasyrov, M.U.; Sachenko, A.V.; Slipokurov, V.S.; Slepova, A.S.; Safryuk, N.V.; Gudymenko, A.I.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Presented in this paper are experimental data on structural properties of contact metallization and temperature dependence of the specific contact resistance for ohmic contacts Au–Ti–Pd–n⁺-InP and Au–Ti–Ge–Pd-n⁺-InP prepared using the method of successive thermal evaporation of metals in oil-free vacuum in one process cycle onto the n⁺-n-n⁺⁺-n⁺⁺⁺-InP epitaxial structure heated to 300 °C. It has been theoretically and experimentally shown that within the temperature range 250…380 K the current transport mechanism in the ohmic contacts Au–Ti–Pd–n⁺-InP is thermal-field one, and in the ohmic contacts Au–Ti–Ge–Pd-n⁺-InP it is caused by conductivity along metal shunts linked with dislocations. According to the X-ray diffraction data, the density of these dislocations in the near-contact InP area is ~10⁹ cm⁻².